COMPOUNDING:CLASSIFICATION OF COMPOUNDS, THEIR STRUCTURAL AND SEMANTIC FEATURES - Khaydarova Nigora; Fayziddinova Munisa (TADQIQOTLAR, 2025)
Abstract This article explores the process of compounding as a productive method of word-formation  in  the  English  language.  It  presents  a  detailed  classification  of compound  words  based  on  their  structural  and  semantic  features,  highlighting distinctions between closed, hyphenated, and open compounds, as well as between endocentric, exocentric, copulative, and appositional types. The paper also analyzes the grammatical behavior, stress patterns, and syntactic roles of compounds in modern English.  The  study  emphasizes  the  importance  of  compounding  in  vocabulary expansion  and  reflects  on  its  growing  role  in  adapting  language  to  cultural  and technological change.